Peningkatan Ekonomi Desa Melalui Pemanfaatan Hasil Laut di Desa Pagagan - Rohmaniyah Rohmaniyah; Nurul Alfian; Syaiful Syaiful (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
Improving the village economy is an important global issue in village economic development in Indonesia. The village economy is a forum for converting opportunities into economic value by carrying out management and operational activities. Operational activities are related to managing input into output by providing added value. Sustainable economic development in villages is important in supporting national economic development. The aim of this activity is that village communities can process marine products in the village so that they have a higher selling value. Apart from that, using marine products can improve the economy so that it can increase people's income. Based on the results of service in Pagagan village, the village economy has improved, and village people can process marine products in Pagagan village so that they have a higher selling value. Apart from that, the use of marine products can improve the economy so that it can increase people's income. Supported by government, non-governmental organizations, and local community initiatives, the village economy can develop significantly, contributing to more equitable national development. Improving the village economy aims to improve community welfare through the natural resources available in the village. Apart from that, economic development in Pagagan village can open up new job opportunities so that the people in the sea will become economically prosperous.